Izbrani mednarodnopravni vidiki državne suverenosti - Pogačnik, Miha (Pravnik, 2016)
The article deals with selected issues of (executing) the sovereignty of the state as an independent body of international law with a special emphasis on the Republic of Slovenia and its way in international relations. With perhaps a slightly critical approach, the author wishes to encourage a deliberation regarding states' sovereign understanding and action in certain situations which Slovenia has faced as a new subject of international law in previous decades. The author's standpoint is: if we have an autonomous, sovereign, and independent state, its sovereignty should be well taken care off.
Keywords: država; mednarodno pravo; state; suverenost